2021
DOI: 10.1021/acs.biochem.0c00877
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosome Core Particles Lacking H2B or H3 Tails Are Altered Structurally and Have Differential Base Excision Repair Fingerprints

Abstract: A recently discovered post-translational modification of histone proteins is the irreversible proteolytic clipping of the histone N-terminal tail domains. This modification is involved in the regulation of various biological processes, including the DNA damage response. In this work, we used chemical footprinting to characterize the structural alterations to nucleosome core particles (NCPs) that result from a lack of a histone H2B or H3 tail. We also examine the influence of these histone tails on excision of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Well-studied PTMs include acetylation, methylation, phosphorylation, ubiquitylation, and ADP ribosylation . Several biochemical experiments on histone tail-less nucleosomes have revealed that histone tails play important roles in the formation of higher-order chromatin structures, as well as in nucleosome structure and stability. These findings strongly suggest that the histone tails themselves play a regulatory role in nucleosome stability, dynamics, and, ultimately, gene expression.…”
mentioning
confidence: 99%
“…Well-studied PTMs include acetylation, methylation, phosphorylation, ubiquitylation, and ADP ribosylation . Several biochemical experiments on histone tail-less nucleosomes have revealed that histone tails play important roles in the formation of higher-order chromatin structures, as well as in nucleosome structure and stability. These findings strongly suggest that the histone tails themselves play a regulatory role in nucleosome stability, dynamics, and, ultimately, gene expression.…”
mentioning
confidence: 99%
“…Globular H2B histones missing the N-terminal tail enhanced excision of εA lesions by DNA-3-methyladenine glycosylase (AAG) due to unwrapping of the DNA in the DNA entry/exit region of the NCP, while globular H3 histones inhibited εA excision by altering DNA periodicity. 3 Taken together, the repair of damaged DNA on NCPs is influenced by the structural and dynamic constraints of DNA–histone interactions and any factor that causes disruption to these interactions.…”
mentioning
confidence: 99%
“…For example, NCPs composed of macroH2A histone variants formed a mixture of octasomes and hexasomes, the latter facilitating the efficient removal of uracil by uracil-DNA glycosylase (UDG) and single-strand-selective monofunctional uracil-DNA glycosylase (SMUG1) in intermediate and low solvent-accessible regions and the dyad axis. Globular H2B histones missing the N-terminal tail enhanced excision of εA lesions by DNA-3-methyladenine glycosylase (AAG) due to unwrapping of the DNA in the DNA entry/exit region of the NCP, while globular H3 histones inhibited εA excision by altering DNA periodicity . Taken together, the repair of damaged DNA on NCPs is influenced by the structural and dynamic constraints of DNA–histone interactions and any factor that causes disruption to these interactions.…”
mentioning
confidence: 99%